Are there any strategies to improve neonatal outcomes associated with epidural analgesia in labor? - Armani, Marta; Gaggiano, Carla; Dallaglio, Sara; Romanini, Enzo; Sospiri, Carmen; Magnani, Cinzia (Acta Biomedica Atenei Parmensis, 2013)
Background and aim of the work: This study was aimed at evaluating the relationship between epidural analgesia and perinatal outcomes and at verifying the advisability of procedural changes in assistance to labor. Subjects and methods: From January to December 2012, we conducted a retrospective case-control study on 1,963 laboring pregnant women admitted to the Parma University Hospital. We considered two groups: Group 1 received epidural analgesia and Group 2 received no analgesia. Women with elective cesarean sections, multiple pregnancies or deliveries at <34 weeks were excluded. We recorded maternal data (age, type of delivery, obstetric procedures, premature rupture of membranes, screenings for Group-B Streptococcus) and neonatal data (birth weight, gestational age, 1- and 5-minute Apgar scores, diagnosis at discharge). Results: Of the 1,963 laboring women, 287 requested analgesia and 1,676 did not. We found no significant differences between the two groups in the rates of cesarean section, clavicle fracture, and 1-minute Apgar score between 4 and 7. By contrast, we observed a higher rate of instrumental deliveries (p<0.01), fetal occiput posterior position (p<0.05), neonatal cephalohematoma (p=0.01) in Group 1 than in Group 2 . In Group 1 we also found a higher number of newborns with 1-minute Apgar score of 3 or less (p=0.016). In addition, a significantly higher number of women in Group 1 had fever during labor (p=0.003, odds ratio 5.01). Conclusions: Our results suggest that strategies should be activated to overcome or limit the side-effects of analgesia in labor through prospective and multidisciplinary studies.